The case of the third national femicide study: Lessons learnt from undertaking research with South African Police Services officials during the COVID-19 pandemic - Manganyi, Tirhani; Ketelo, Asiphe; Gounden, Tholsie; Mabhida, Mpumelelo; Majola, Thobeka; Variava, Tarique; Mhlongo, Shibe; Dekel, Bianca (SA crime quarterly, 2024)
Collecting South African Police Service’s (SAPS) data is critical for femicide research in South Africa. This paper outlines lessons learnt from interviews with SAPS officials during the COVID-19 pandemic to collect data for the third national femicide study. This paper is based on the shared experiences of the research team, particularly the fieldworkers, and provides insight into undertaking research with the SAPS. It guides researchers, especially those planning to conduct researcher-administered questionnaires with SAPS officials. This paper also provides insight into the complexities and sheds light on the intricacies behind the hierarchical structure of the SAPS. It further suggests ways to improve both face-to-face and telephonic data collection and strategies to reduce missing data. The paper also highlights the need to be flexible and creative in devising strategies to overcome challenges. Finally, the paper addresses the various methods used to resolve challenges and enable the project to collect the best quality data with the least disruption to the services provided by SAPS officials.